Redacting Acts: The Acts of the Apostles in the Three-Year Lectionaries. (September 2021) - Connell, Martin
The representation of the Acts of the Apostles in the three-year lectionaries—the Roman Catholic Ordo Lectionum Missae (OLM) and the Protestant Revised Common Lectionary (RCL)—favors the first half of the twenty-eight-chapter book over its second half. The OLM prescribes nine times more verses from the first half than from the second half, and the RCL prescribes four times more. This article compares the proportion of Acts in the lectionaries to the other twenty-six books of the New Testament, shows when in the three-year lectionary cycle readings from Acts are proclaimed, presents how much of each of the twenty-eight chapters of Acts appears in the lectionaries, hypothesizes about why the second half of Acts is slighted, and argues that the church's liturgical tradition is weakened by muting significant passages about post-resurrection eucharists.